The Influence Of The Human Development Index And The Rate Of Open Unemployment On The Number Of Poor Population In Lamongan District - Ririn Aprilia Dewanti; Sishadiyati Sishadiyati (International Journal of Economics, Business and Innovation Research, 2024)
Sustainable Development Goals (SDGs) or Sustainable Development is a global and national commitment to improve people's welfare, which includes 17 goals until 2030. The main goal emphasized by the SDGs is "No Poverty" or "eliminate poverty". Poverty is closely related to vulnerability. Vulnerability itself is a condition that arises due to the inability to meet needs so that it can cause the emergence of new social problems in life, so the study of poverty is often referred to as an "eternal study" that is ongoing and needs to find a solution. The aim of this research is to see how much influence the Human Development Index and Open Unemployment Rate have on the number of poor people in Lamongan Regency. This research uses time series data which is then analyzed using multiple linear regression analysis. The results of this research show that the Human Development Index (HDI) has asignificant influence on the number of poor people in Lamongan Regency. Meanwhile, the Open Unemployment Rate (TPT) has no significant effect on the number of poor people in Lamongan Regency.